1997
DOI: 10.4315/0362-028x-60.9.1034
|View full text |Cite
|
Sign up to set email alerts
|

Growth Media and Surface Conditioning Influence the Adherence of Pseudomonas fragi, Salmonella typhimurium, and Listeria monocytogenes Cells to Stainless Steel

Abstract: Microorganisms have been shown to adhere to food-contact surfaces and may provide a route for the contamination of processed food. To better understand this phenomenon, the effects of growth media and surface conditioning on the adherence of Pseudomonas fragi, Salmonella typhimurium and Listeria monocytogenes cells to stainless steel were studied. The microorganisms were grown in tryptic soy broth (TSB), 1% reconstituted skim milk (RSM) and RSM with 1% sucrose (RSM + S). Stainless-steel surfaces were condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…3a). Hood and Zottola (17) found that, for some bacteria like Salmonella enterica serovar Typhimurium, adhesion to stainless steel was similarly facilitated by an initial organic layer, whereas higher numbers of both Pseudomonas fragi and L. monocytogenes bacteria were found on noncondi- tioned surfaces. Some food components, e.g., milk proteins, may actually decrease attachment of bacteria (2).…”
Section: Discussionmentioning
confidence: 99%
“…3a). Hood and Zottola (17) found that, for some bacteria like Salmonella enterica serovar Typhimurium, adhesion to stainless steel was similarly facilitated by an initial organic layer, whereas higher numbers of both Pseudomonas fragi and L. monocytogenes bacteria were found on noncondi- tioned surfaces. Some food components, e.g., milk proteins, may actually decrease attachment of bacteria (2).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this fact, the conventional sanitation and disinfectant agents may fail to kill bacteria under certain conditions (Hodd & Zottola 1997). Moreover, it was found that the cell-to-cell DNA transmission occurs in a micro-community, and the biofilm development can be stimulated by their conjugation mechanism (Molin & Tolker-Nielsen 2003).…”
mentioning
confidence: 99%
“…Nessas condições, os resultados da literatura deixam claro que a eficácia dos desinfetantes, aplicados tanto à microbiota natural quanto à cepas de microrganismos artificialmente inoculadas em superfícies de frutas e verduras, é muito menor do que nos testes de suspensão. Além disso, mesmo que a característica de resistência das cepas aos diferentes princípios ativos dos desinfetantes seja similar, as diferenças nas características de adesividade e formação de biofilmes podem interferir na eficácia dos desinfetantes [1,13,20,23,27,29,35,37,45] Outro fator importante a considerar é o fato de desinfetantes com o mesmo princípio ativo, porém, de marcas comerciais distintas, apresentarem diferença na eficácia antimicrobiana [17]. Assim, é imprescindível o monitoramento periódico da qualidade dos produtos disponíveis no mercado, para garantir segurança dos tratamentos de desinfecção aplicados.…”
Section: Resistência Aos Sanitizantesunclassified